การใช้พื้นที่สาธารณะในเมืองเชียงใหม่ กรณีกาดเช้าเกษตรชุมชนปลอดสารพิษ ถนน 2 เชียงราย - กาญจนาถ ทองชัยประสิทธิ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This independent study is the study of public space in a present day, which raises the question about the meaning and function of public space. The purpose of this study is 1. to categorize and analyze the concepts of public space 2. to analyze and critique the meaning and using public spaces in Muang Chiang Mai. 3. to provide guidelines for designing public space based on the notion of Space of Tactics. Using Chang Kian Market as the case study, the researcher argues for a new form of public space situated by the relationship between the people and the area on a daily basis. In order to avoid the confrontation with the public and local authorities, tactic practices are normally used in public space in Thailand. Chiang Kien Market is regarded as a conceptual model in order to decode some of the specific tactic to use for an experimental design. Partially this study explores Chiang Kien Market to find a way of how to design public space applying to the Case of Safety Agriculture Community Morning Market Thanon 2 Chiang Rai. The public areas are as vibrant and according to everyday life conditions. Part of this research is an experimental design by using guidelines base on 4 items. There are access and visibility, talking space, environment and human scale that can be summarized into three main factors. 1. The dimension of time to comply with the activities. 2. Creating a space related to the context of both vertical and horizontal, including the level of the roof that depends on the activity or the proportion of users, product display and placement. The degree of alignment of vision and relationships horizontally like a boundary. To facilitate the use of natural boundaries, such as the shade of a tree or a building. 3. To consider about the cultural dimension of this space such as the people in relation to the community, ownership, and a natural setting. The completed guideline will be fosters the development of new ideas to applied in designing urban solutions. In conclusion, the researcher found that the guidelines for the design of public space could be done. The experiment found that the public space design base on the concept of tactic space is to apply using public space by questioning the rules and conditions of the area (Tactical area). The researcher found that if the tactics happen at the right place right time. It could offer the place to be publicized and eventually become a successful public space.